(untitled) (Fiep Bulletin - online, 2011)
The constant search for better survival conditions has led the working class to change habits that overload your day to day work and obligations. The class of teacher is no exception to this feature by extending their workday at home, and also to submit to the bad working conditions offered, which include professional devaluation and the daily stresses caused by a series of negative factors that extends from the political to social sphere. By investigating the lifestyle using the Pentacle Welfare of a group of 101 teachers from public and private school in the city of Tupa SP, can be seen that a significant percentage of teachers from both school systems, public and private responded negatively to some statements in the questionnaire, especially the components Nutrition, Physical Activity and Stress Control. The results showed that these teachers, go to a quality of life lower than recommended, which may in the near future, if it is not, are suffering from ailments that could influence not only their professional lives, but also the human being behind the profession.